"We flew under the radar:" examining the influence of stigma on community engagement strategies among harm reduction practitioners in Central Appalachia - Claire G. Hoffman; Kathryn E. Moracco; Blythe E. Rhodes; Clare L. Barrington; Regina Musa; Leah K. Taraskiewicz (Elsevier, 2023)
Background: The rise in opioid overdoses has disproportionately affected the Central Appalachian region of the United States. Stigma towards people who use drugs (PWUD) has limited access to life-saving harm reduction services in the region. Previous research has emphasized the need to engage communities to reduce stigma, yet these efforts can lead to backlash. The purpose of this study was to explore how stigma affects harm reduction practitioners' approaches to community engagement. Methods: We analyzed qualitative interviews with harm reduction practitioners (n ​= ​35) in Central Appalachia. We used deductive and inductive coding, as well as narrative summaries, to identify harm reduction practitioners' descriptions of stigma and their resulting approaches to community engagement. We identified three in vivo codes that encapsulated the main community engagement strategies, "flying under the radar," "spreading the word," and "damage control," and assessed how each strategy influenced program operations. Results: Most participants (n ​= ​18) "spread the word," or conducted community engagement activities to combat social stigma about harm reduction services. While many were able to gain approval in the community, some experienced pushback from certain stakeholders. Eleven participants "flew under the radar," or decided not to engage stakeholders about their program, after perceiving that social and enacted stigma were too great to overcome. While they did not experience backlash, they could not access some funding sources or partner with state-sanctioned organizations. Finally, a few participants (n ​= ​6) did not proactively choose an engagement approach and instead had to conduct "damage control" to assuage community concerns about their services. Conclusion: To determine the most appropriate engagement strategy, harm reduction practitioners may benefit from evaluating the levels of stigma within their community. Federal, state, and local funding and policy interventions are needed to augment stigma reduction efforts within Central Appalachia.